Cousins not twins: intratumoural and intertumoural heterogeneity in syndromic neuroendocrine tumours. Issue 3 (13th May 2017) - Flynn, Aidan; Dwight, Trisha; Benn, Diana; Deb, Siddhartha; Colebatch, Andrew J; Fox, Stephen; Harris, Jessica; Duncan, Emma L; Robinson, Bruce; Hogg, Annette; Ellul, Jason; To, Henry; et al.
Abstract: Hereditary endocrine neoplasias, including phaeochromocytoma/paraganglioma and medullary thyroid cancer, are caused by autosomal dominant mutations in several familial cancer genes. A common feature of these diseases is the presentation of multiple primary tumours, or multifocal disease representing independent tumour clones that have arisen from the same initiating genetic lesion, but have undergone independent clonal evolution. Such tumours provide an opportunity to discover common cooperative changes required for tumourigenesis, while controlling for the genetic background of the individual. We performed genomic analysis of synchronous and metachronous tumours from five patients bearing germline mutations in the genes SDHB, RET, and MAX . Using whole exome sequencing and high‐density single‐nucleotide polymorphism arrays, we analysed two to four primary tumours from each patient. We also applied multi‐region sampling, to assess intratumoural heterogeneity and clonal evolution, in two cases involving paraganglioma and medullary thyroid cancer, respectively. Heterogeneous patterns of genomic change existed between synchronous or metachronous tumours, with evidence of branching evolution. We observed striking examples of evolutionary convergence involving the same rare somatic copy‐number events in synchronous primary phaeochromocytoma/paraganglioma. Convergent events also occurred during clonal evolution of metastatic medullary thyroid cancer. These observations suggest that genetic or epigenetic changes acquired early within precursor cells, or pre‐existing within the genetic background of the individual, create contingencies that determine the evolutionary trajectory of the tumour. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.